The use of Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange (THRIVE) to facilitate Tracheostomy under sedation. Issue 1 (26th January 2016) - Abeysundara, Lasitha; Parker, Helen; Fowler, Anna; Patel, Anil
Summary: Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange (THRIVE) is an apnoeic oxygenation technique which has also been observed to allow a degree of carbon dioxide clearance [1]. We present the case of a 61‐year‐old patient with impending complete upper airway obstruction secondary to an advanced supraglottic neoplasm, precluding orotracheal intubation. The patient became agitated during tracheostomy under local anaesthesia and required sedation to the point of apnoea in order to complete the procedure safely. The use of THRIVE throughout this case was invaluable in bridging periods of ensuing hypoventilation and apnoea, preventing oxygen desaturation and hypercarbia.